2020
DOI: 10.1002/mus.26800
|View full text |Cite
|
Sign up to set email alerts
|

7T MR neurography‐ultrasound fusion for peripheral nerve imaging

Abstract: Background We present one patient with an initial diagnosis of Guillain‐Barré syndrome (GBS) and one with Charcot–Marie–Tooth disease (CMT) type 1A. Methods Both patients underwent ankle tibial nerve fusion‐imaging of high‐resolution ultrasound (HRUS) with 7T MR neurography (MRN). Results In GBS, the nerve was enlarged, T2‐hyperintense, and showed increased vascularization 21 months after symptom onset. In CMT1A, the enlarged nerve was T2‐isointense with normal endoneurial blood flow. Conclusions We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ziff et al identified pachymeningeal thickening in POEMS syndrome patients in contrast to patients with CIDP [26]. Combining HRUS and MRI might help to achieve even greater diagnostic accuracy, but future systematic studies are needed to prove this hypothesis [27]. MRI, especially diffusion tensor imaging (DTI) based tractography, might be used in the future to verify measurements by HRUS.…”
Section: Discussionmentioning
confidence: 99%
“…Ziff et al identified pachymeningeal thickening in POEMS syndrome patients in contrast to patients with CIDP [26]. Combining HRUS and MRI might help to achieve even greater diagnostic accuracy, but future systematic studies are needed to prove this hypothesis [27]. MRI, especially diffusion tensor imaging (DTI) based tractography, might be used in the future to verify measurements by HRUS.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers made further investigations and found other applications of the method in neurology. [10] These authors used 7T MR neurography-ultrasound fusion for peripheral nerve imaging. They demonstrated the utility of UFI system for more accurate identification of Guillain-Barré syndrome and Charcot-Marie-Tooth disease type 1A.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of combining both technologies is that they can compensate each other's limitations (HRUS: displaying distal nerves, nerve vascularization, long-distance nerve segments; MRN: showing blood-nerve barrier breakdown through T2 sequences, proximal nerve segments). Combining HRUS and MRN and applying new imaging markers might thereby be a promising approach to achieve even more conclusive and diagnosis-guiding results [14,39,40]. Of course, future systematic studies have to prove if combining both technologies will improve diagnostic accuracy [40].…”
Section: Discussionmentioning
confidence: 99%
“…Combining HRUS and MRN and applying new imaging markers might thereby be a promising approach to achieve even more conclusive and diagnosis-guiding results [14,39,40]. Of course, future systematic studies have to prove if combining both technologies will improve diagnostic accuracy [40]. Still, combining clinical examination, nerve conduction studies and HRUS is sufficient for the diagnosis of immune-mediated neuropathies in some cases and MRN is hence not necessary [13].…”
Section: Discussionmentioning
confidence: 99%